2021
DOI: 10.1093/jpp/rgaa056
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin attenuates inflammation and modulates Nrf2/caspase-3 signalling in STZ-induced aortic injury

Abstract: Objectives The current study provides evidence on the ameliorative impact of Isoliquiritigenin (ISL), a natural bioflavonoid isolated from licorice roots against diabetes mellitus (DM)-induced aortic injury in rats. Methods DM was induced in male Sprague–Dawley rats by single I.P. injection of STZ (50 mg/kg). ISL was administrated daily (20 mg/kg, orally) for 8 wks. Key findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Previous studies have confirmed that Nrf2 is an important target against oxidative stress. 16 , 23 , 24 Given that Nrf2 mainly enters the nucleus to exert its biological functions, 16 we detected Nrf2 level in the nucleus after AMI. Western blot analysis showed that the level of Nrf2 in the nucleus and its downstream target HO-1 were increased due to oxidative stress ( Figure 5A and B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have confirmed that Nrf2 is an important target against oxidative stress. 16 , 23 , 24 Given that Nrf2 mainly enters the nucleus to exert its biological functions, 16 we detected Nrf2 level in the nucleus after AMI. Western blot analysis showed that the level of Nrf2 in the nucleus and its downstream target HO-1 were increased due to oxidative stress ( Figure 5A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…ISL has been extensively studied in multiple pathological processes, such as diabetic cardiomyopathy 23 and intracerebral hemorrhage. 25 The main function of ISL is to counteract oxidative stress and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3 and Caspase-9 are involved in signal transduction of the death receptor apoptosis pathway and mitochondrial apoptosis pathway, respectively [ 20 ]. Finally, caspase-3 is activated and apoptosis is performed through cascade activation of multiple downstream caspase molecules [ 21 , 22 ]. Paeoniflorin is the active ingredient of Paeonia lactiflora, which can protect cells from inflammation and oxidation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antidiabetic and antidepressant profile of MSE is obviously supported by its chemical constituents. For instance, isoliquiritigenin attenuated DM-induced renal and aortic injury, and displayed significant neuroprotective and antidepressant effects via its effects of oxidative stress and inflammation [ 45 , 46 , 47 ]. Silvestro et al reported that quercetin displayed antidepressant-like actions due to its antioxidant, anti-inflammatory and neuroprotective effects in several animal models [ 48 ].…”
Section: Discussionmentioning
confidence: 99%